SOCIOLOGICAL ANALYSIS OF THE ACTIVITIES OF CHARISMATIC PERSONALITIES IN PUBLIC ADMINISTRATION (Scientific journal of the Fergana State University, 2026)
This article examines some aspects of the activities of political figures in public administration, the charisma of leaders and their qualities. The role of political leaders in the development of society and the research of famous sociologists in this area are analyzed.